Improved Survival of a HER2-Positive Metastatic Breast Cancer Patient Following a Personalized Peptide Immunization - Schönharting, Wolfgang; Roehnisch, Tim; Manoochehri, Mehdi; Christoph, Jan; Sieger, Marie; Nogueira, Mauro; Martos-Contreras, Mari Carmen; Kunz, Meik (Vaccines, 2023)
Cancer neoantigens that arise from somatic mutations have emerged as important targets for personalized immunization. Here, we report an improved overall survival of a HER2-positive metastatic breast cancer patient using a bioinformatic-based personalized peptide immunization called BITAP (BioInformatic Tumor Address Peptides). The epitopes were predicted using our in-house bioinformatic pipeline, and the immunogenicity was tested by IFN-γ ELISPOT and intracellular cytokine staining assays. In total, a significant peptide-specific T-cell response was detected against 18 out of the 76 (≈24%) tested peptides. The patient’s follow-up by measuring serologic markers showed a significant reduction in the tumor marker levels following BITAP immunization. Along with standard treatment, the patient treated with the BITAP showed stable disease with a remarkably improved overall survival, and no serious treatment-related adverse effects. In conclusion, our findings suggest that BITAP immunization is feasible, and safe, and may induce tumor regressions in patients with HER2-positive subsets of breast cancer.
CRIS-Team Scopus Importer:2024-12-16
Keywords: bioinformatics; breast cancer; case report; immunotherapy; neoantigen; peptide